2016
DOI: 10.1021/acs.nanolett.5b05283
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Effects of Inorganic Components in Solid Electrolyte Interphase on High Cycle Efficiency of Lithium Ion Batteries

Abstract: The solid electrolyte interphase (SEI), a passivation layer formed on electrodes, is critical to battery performance and durability. The inorganic components in SEI, including lithium carbonate (Li2CO3) and lithium fluoride (LiF), provide both mechanical and chemical protection, meanwhile control lithium ion transport. Although both Li2CO3 and LiF have relatively low ionic conductivity, we found, surprisingly, that the contact between Li2CO3 and LiF can promote space charge accumulation along their interfaces,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
294
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 362 publications
(311 citation statements)
references
References 40 publications
(115 reference statements)
6
294
1
Order By: Relevance
“…This could be due to defects or band-bending on grain boundaries inside the SEI. Interface effects on such boundaries can promote lithium-ion and potentially electron mobility as shown by Zhang et al 20 We highlight that the specific transport mechanism used does as demonstrated by replacing conduction with neutral lithium interstitial diffusion. Any mechanism which transports charges though the SEI for the reduction of the solvent at the SEI/electrolyte interface will produce qualitatively similar results.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This could be due to defects or band-bending on grain boundaries inside the SEI. Interface effects on such boundaries can promote lithium-ion and potentially electron mobility as shown by Zhang et al 20 We highlight that the specific transport mechanism used does as demonstrated by replacing conduction with neutral lithium interstitial diffusion. Any mechanism which transports charges though the SEI for the reduction of the solvent at the SEI/electrolyte interface will produce qualitatively similar results.…”
Section: Discussionmentioning
confidence: 70%
“…We consider a large volume V a 3 0 in which all sub-cubes are randomly assigned to SEI/pores with uniform probability ε SEI /ε. The total surface area in V can be approximated as [20] where V a…”
Section: Journal Of the Electrochemical Society 164 (11) E3132-e3145mentioning
confidence: 99%
“…Different components in the SEI, as well as their properties, influence the performance of SEI in coordinated complex ways. 8,25,34 The progressive understanding of SEI over the past 50 years has been summarized in Fig. 2.…”
Section: Solid Electrolyte Interphase (Sei) In Li-ion Batteriesmentioning
confidence: 99%
“…38,169,179 Another method to increase the diffusion carrier concentration is taking advantage of the space charge layer effect 184 created by heterogeneous structures and grain boundaries. 34,185 Given the difference of the Li diffusion carriers in Li 2 CO 3 and LiF, Pan et al 185 combined the DFT predicted interfacial defect reaction energetics and the continuum Poisson-Boltzmann relationship to understand the effect of mixing LiF and Li 2 CO 3 on Li-ion conductivity. They found that a space charge layer is formed via the defect reaction across the Li 2 CO 3 and LiF interface, which results in the dramatically increased Li-ion interstitial concentration in Li 2 CO 3 and an increased Li vacancy concentration in LiF, as illustrated in Fig.…”
Section: Correlation Of Sei Properties With Battery Performance Starmentioning
confidence: 99%
See 1 more Smart Citation